Governance, inequality and inclusive education in Sub-Saharan Africa - Simplice Asongu; Samba Diop; Amsalu K. Addis (African Governance and Development Institute (AGDI), 2020)
The study provides thresholds of income inequality that if exceeded will nullify the positive effect of governance dynamics on gender-inclusive education in 42 countries in sub-Saharan Africa for the period 2004-2014. The Generalised Method of Moments is used as an estimation strategy. The following findings are established. First, the unconditional effects of governance dynamics on inclusive education are consistently positive whereas the corresponding conditional effects from the interaction between inequality and governance dynamics are consistently negative. Second, the levels of inequality that completely crowdout the positive incidence of governance on inclusive "primary and secondary education" are: 0.587 for the rule of law and 0.565 for corruption-control. Third, the levels of inequality that completely dampen the positive incidence of governance on inclusive "secondary education" are: 0.601 for "voice & accountability" and 0.700 for regulation quality. Fourth, for tertiary education, inequality thresholds are respectively 0.568 for political stability and 0.562 for corruption-control. The main policy implication is that for governance dynamics to promote inclusive education in the sampled countries, income inequality levels should be kept within the established thresholds. Other implications are discussed in the light of Sustainable Development Goals.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Inequality; Gender; Inclusive development